Impact of Neuroscience-Based Interventions on Early Learning (Docentes 2.0 Journal, 2026)
In recent years, the application of neuroscience in education has grown significantly because it explains how the brain learns. This research aimed to systematize the available empirical evidence on the impact of neuroscience-based interventions for early learning. The study adopted a hermeneutic-interpretive paradigm, a systemic method, a qualitative approach, a thematic narrative design, a documentary-bibliographic review design, and a cross-sectional scope. The search covered Scopus, Web of Science (WoS), and Google Scholar, and the final sample comprised 14 articles. The review used Covidence and the PRISMA technique for selection and analysis through a three-level flow. The findings indicated that interventions such as emotional regulation and executive function programs, kinesthetic and sensorimotor activities, and multisensory/technology-assisted interventions were grounded in principles of neuroplasticity, sensory stimulation, emotional co-regulation, and sensorimotor integration. These interventions produced positive effects on early learning and on specific areas such as cognitive, socioemotional, and motor development, and most studies used experimental and quasi-experimental designs with pre- and post-intervention assessments in children aged 0 to 6 years. The review concluded that this intervention approach strengthens child well-being and supports the design of learning environments that are more responsive to the needs of comprehensive development in early childhood.
Keywords: Interventions; neuroscience; early learning; impact; systematic review